From Jan Sunwai to Rajasthan Right to Hearing Act 2012: Fostering Transparency and Accountability through Citizen Engagement. (December 2018) - Agrawal, Vidhi; Nair, Hari
This study examines the evolution of the movement for transparency towards redressing grievances and holding public servants accountable to the people. It explains how three legislations—Right to Information Act (RTI, India, 2005), Rajasthan Guaranteed Delivery of Public Services Act (RGDPS, 2011) and the Right to Hearing Act (RTH, Rajasthan, 2012)—form part of a continuum in the people's struggle for transparency. The analysis of the three acts as a continuum is significant because together these are gradually changing the administration-centric Indian polity into a citizen-centric one. If the RTI Act ensured an informed citizenry, the RGDPS Act recognized the government's duty to provide public services and the RTH Act guaranteed that the people were heard by the government. This right to hearing may be traced back to the Jan Sunwai, which was a pivotal forum in the struggle for transparency because it functioned as a dialogical space between the people and the state, as well as a forum for social auditing and civic engagement. Of late however, the Jan Sunwai is being transformed by digital technology. This transformation poses the challenge of converting a participatory polity alive with people's voices into a transactional state regimented by technology.